Composite sulfide solid electrolyte material, preparation method and application
By introducing quantum dots into sulfide solid electrolyte materials and hot press sintering treatment, the problems of quantum dot dispersion and stability are solved, and higher ionic conductivity and interface stability are achieved, making it suitable for solid-state batteries.
Patent Information
- Application Number
- CN202510112559.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-24
AI Technical Summary
When dispersing quantum dots, existing sulfide solid electrolyte materials have problems such as difficulty in ensuring dispersion and difficult to maintain surface modification stability for a long time, resulting in inconsistent ion transport efficiency and electrolyte performance.
By mixing the precursor material and the quantum dot material and subjecting to hot-press sintering treatment, a composite sulfide solid electrolyte material modified with quantum dots is prepared to ensure uniform distribution of quantum dots in the sulfide matrix.
It significantly improves the ionic conductivity and interface stability of the material, improves ionic conductivity, interface compatibility, mechanical properties and electrochemical stability, reduces costs, and is suitable for large-scale production.
Smart Images

Figure CN119551637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy materials, and in particular to a composite sulfide solid electrolyte material, a preparation method and an application thereof. Background Art
[0002] With the continuous growth of energy demand and the increasingly severe environmental problems, the development of energy storage devices with high energy density, high safety and long life has become an urgent need. Solid-state batteries are considered to be the development direction of the next generation of energy storage devices because they use solid electrolytes instead of traditional liquid electrolytes, have higher safety, wider electrochemical window and higher energy density. However, solid-state electrolyte materials still face some challenges.
[0003] Although oxide solid electrolytes have high ionic conductivity, they are brittle, difficult to process, and have high interface impedance, which limits their application in solid-state batteries. Although polymer solid electrolytes have good flexibility and processing properties, their ionic conductivity is low and it is difficult to meet the needs of high power density solid-state batteries. Sulfide solid electrolytes have become one of the most promising solid electrolyte materials due to their advantages such as high ionic conductivity, good flexibility and good contact with electrodes. As a new type of nanomaterial, quantum dots have unique physical and chemical properties, such as high specific surface area and adjustable electronic energy level structure, and have also become potential materials for improving solid electrolyte materials. However, in research, it was found that the dispersibility of quantum dots in solid electrolytes is difficult to ensure, and agglomeration is prone to occur, thereby affecting the ion transmission efficiency and the consistency of electrolyte performance. In order to improve these shortcomings, some measures have been taken in the prior art, such as improving the dispersibility of quantum dots in solid electrolyte materials by adding dispersants, and enhancing their compatibility with solid electrolytes by surface modification of quantum dots, etc. However, these methods still have some disadvantages, such as limited dispersion effect and difficulty in maintaining the stability of surface modification for a long time. Another common improvement measure is the co-precipitation method, but this method is very sensitive to reaction conditions such as temperature, pH value, precipitant addition rate and concentration, and other parameters. Slight changes in process parameters may lead to large differences in the distribution and performance of quantum dots in solid electrolytes. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a composite sulfide solid electrolyte material, a preparation method and an application thereof.
[0005] The objective of the present invention is achieved through the following technical solutions: <First aspect> The present invention provides a method for preparing a composite sulfide solid electrolyte material modified with quantum dots, which comprises mixing a precursor material and a quantum dot material, and then performing a hot pressing sintering treatment to obtain the composite sulfide solid electrolyte material, wherein: The mass ratio of the precursor material to the quantum dot material is 100: (1-10); The precursor material is a general formula Li x M y S b One or more of the sulfide materials shown are mixed, or the mixed sulfide materials have a general formula of Li x M y S b It is composed of two or more materials with the same element ratio, M is one of P, Si and Ge, x:y:b=(1.3~2.4) : 1 : (2.6~3.7); Quantum dot materials are metal compound quantum dots or carbon quantum dots with semiconductor properties.
[0006] As an embodiment, the precursor material is composed of Li2S and a sulfide of element M in a mass ratio of (0.45~0.7):1, and M is one of P, Si, and Ge.
[0007] As an embodiment, the sulfide of element M is P2S5, SiS2 or GeS2.
[0008] In some embodiments, the precursor material is Li2S and P2S5 in a mass ratio of 0.48:1.
[0009] In some embodiments, the precursor material is Li2S and SiS2 in a mass ratio of 0.49:1.
[0010] In some embodiments, the precursor material is Li2S and GeS2 in a mass ratio of 0.67:1.
[0011] As an embodiment, the average particle size of the quantum dot material is 1 to 100 nm.
[0012] As an embodiment, the average particle size of the quantum dot material is 1 to 50 nm.
[0013] In some embodiments, the average particle size of the quantum dot material is 2-20 nm.
[0014] As an embodiment, the metal compound quantum dots are metal sulfides.
[0015] As an embodiment, the metal compound quantum dots are one or more of Ag2S, Cu2S, CdS, ZnS, and PbS.
[0016] As an embodiment, the carbon quantum dots are one or more of graphene quantum dots and carbon nanotube quantum dots.
[0017] In some embodiments, the quantum dot material is Ag2S, CdS or carbon nanotube quantum dots.
[0018] As an embodiment, the mass ratio of the precursor material to the quantum dot material is 100: (1~5).
[0019] As an embodiment, the hot pressing sintering parameters are: in an inert atmosphere, a pressure of 400-450 MPa, a temperature of 230-300° C., and a time of 4-7 h.
[0020] In some embodiments, the hot pressing sintering parameters are: in an inert atmosphere, a pressure of 420 MPa, a temperature of 240° C., and a time of 7 h.
[0021] As an embodiment, the precursor material is obtained by ball milling Li2S and sulfide of element M.
[0022] As an embodiment, the mixture of the precursor material and the quantum dots is processed by ball milling.
[0023] As an embodiment, the ball milling jar and the grinding balls in the ball milling process are both made of zirconium oxide.
[0024] As an implementation scheme, the parameters of the ball milling treatment are: ball-to-material ratio is (15~40): 1, and the ball milling time is 15~30 h.
[0025] As an embodiment, the ball milling treatment is planetary ball milling treatment, and the rotation speed is 500-650 revolutions per hour.
[0026] In some embodiments, the ball milling process for preparing the precursor material is planetary ball milling.
[0027] In some embodiments, the parameters of the ball milling process when preparing the precursor material are: ball-to-material ratio is 23:1, rotation speed is 500 rpm, and ball milling time is 25 h.
[0028] As an embodiment, the ball milling treatment of the precursor material and quantum dots is performed by vibration ball milling.
[0029] As an embodiment, the parameters of the vibration ball milling treatment are: the vibration frequency is 1500~2000 rpm.
[0030] In some embodiments, the parameters of the vibration ball milling process are: ball-to-material ratio is 20:1, vibration frequency is 1800 rpm, and ball milling time is 20 h.
[0031] <Second Aspect> The present invention provides a method for preparing a composite sulfide solid electrolyte membrane modified with quantum dots, which is further prepared based on the above-mentioned composite sulfide solid electrolyte material modified with quantum dots, comprising: After step S3, add: S4, grinding the sintered product to obtain electrolyte powder; S5. Coating the slurry obtained by mixing the electrolyte powder, the binder and the solvent on a substrate under an inert atmosphere, and after drying, the composite sulfide solid electrolyte membrane can be formed on the substrate.
[0032] As an embodiment, the electrolyte powder has a particle size of micrometer level.
[0033] As an embodiment, the electrolyte powder has a particle size of 200-500 μm.
[0034] As an embodiment, the grinding process is a roller crushing method, with a roller speed of 50-100 rpm and a pressure of 3-5 MPa.
[0035] In some embodiments, the grinding process parameters are: roller speed of 70 rpm and pressure of 3 MPa.
[0036] As an embodiment, the mass ratio of the electrolyte powder, the binder and the solvent is (70~95): (5~30): 100.
[0037] As an embodiment, the binder is selected from one or more of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, and polymethyl methacrylate.
[0038] In some embodiments, the binder is polyvinylidene fluoride.
[0039] As an embodiment, the slurry is mixed using a drum ball mill or a shearing machine for 10 to 15 hours.
[0040] As an embodiment, the coating is performed by uniformly coating the slurry on the substrate in an inert atmosphere.
[0041] As an embodiment, the drying is carried out in an inert atmosphere at 70°C.
[0042] In some embodiments, the substrate is made of copper tape with a parameter of 10 μm.
[0043] <Third Aspect> The present invention provides a composite sulfide solid electrolyte material, including: a general formula Li x M y N c S z For the substance shown, M is one of P, Si, and Ge, N is one of Ag, Cd, Zn, Pb, and C, and x:y:c:z=(1.3~2.4) : 1 : (0.01~0.6) : (2.6~3.7).
[0044] <Fourth Aspect> The present invention provides an application of a composite sulfide solid electrolyte material in an all-solid-state soft-pack battery.
[0045] As an embodiment, the all-solid-state soft-pack battery includes: a positive electrode, a negative electrode, and an electrolyte membrane prepared from the composite sulfide solid electrolyte material.
[0046] As an embodiment, the negative electrode includes lithium metal or a lithium metal composite.
[0047] As an embodiment, the positive electrode comprises NCM811.
[0048] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a composite sulfide solid electrolyte material. Through the step-by-step ball milling method, the mixing process of raw materials can be better controlled. The sulfide is firstly ball-milled to achieve a certain particle size and uniformity, and then quantum dots are added for the second stage of ball milling, which can ensure the uniform distribution of quantum dots in the sulfide matrix to achieve better mixing performance optimization.
[0049] Furthermore, the present invention also provides a method of reducing the activation energy of the reaction by ball milling the reactants, thereby initiating the reaction to form a sulfide solid electrolyte precursor, and then adding quantum dots for further processing, so that the final solid electrolyte material has a more uniform composition and structure, and further sintering is performed to form a good interface contact between the quantum dots and the sulfide material.
[0050] The present invention can significantly improve the ionic conductivity and interface stability of the material by introducing semiconductor quantum dots (such as metal compound quantum dots or carbon quantum dots) into the sulfide solid electrolyte, as follows: (1) Higher ionic conductivity: The introduction of quantum dots can increase the interfacial area in the composite solid electrolyte membrane, promote the transmission and diffusion of lithium ions, and thus improve the ionic conductivity. In addition, quantum dots can interact with the sulfide matrix, change the electronic structure of the matrix, and further improve the ionic conductivity.
[0051] (2) Better interface compatibility: Quantum dots can act as interface modifiers to improve the interface contact between the composite solid electrolyte membrane and the electrode, reduce the interface impedance, and improve the cycle stability and rate performance of solid-state batteries.
[0052] (3) Enhanced mechanical properties: The introduction of polymer binders and quantum dots can enhance the mechanical strength and toughness of the composite solid electrolyte membrane, making it more resistant to volume changes during the charging and discharging process of the solid-state battery and reducing the short-circuit risk of the solid-state battery.
[0053] (4) Higher electrochemical stability: Quantum dots can act as stabilizers to inhibit the decomposition and side reactions of the sulfide matrix during the electrochemical cycle, thereby improving the electrochemical stability of the solid electrolyte and extending the life of the solid-state battery.
[0054] (5) Lower cost: The preparation cost of quantum dots is relatively low, and the preparation method provided by the present invention is simple and easy to implement, suitable for large-scale production. Therefore, it can reduce the manufacturing cost of solid-state electrolytes and promote the commercial application of solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 is the XRD pattern of the electrolyte powder obtained in step S4 of Example 1 of the present invention; Figure 2 is the XRD pattern of the electrolyte powder obtained in step S4 of Example 2 of the present invention; Figure 3 is the XRD pattern of the electrolyte powder obtained in step S4 of Example 3 of the present invention; Figure 4 is the XRD pattern of the electrolyte powder obtained in step S4 of Example 4 of the present invention; Figure 5 is the XRD pattern of the electrolyte powder obtained in step S4 of Example 5 of the present invention; Figure 6 is the XRD pattern of the electrolyte powder obtained in step S4 of Comparative Example 1 of the present invention; Figure 7 is the XRD pattern of the electrolyte powder obtained in step S4 of Comparative Example 2 of the present invention; Figure 8 This is the XRD diagram of the electrolyte powder obtained in step S4 in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0056] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0057] Example 1 This embodiment provides a method for preparing a quantum dot Ag2S modified Li-PS composite sulfide solid electrolyte membrane, and the raw materials used include: Sulfide electrolyte precursor: Li2S and P2S5 with a mass ratio of 0.48:1; Quantum dots: Ag2S, average particle size 10 nm; Polymer: polyvinylidene fluoride (PVDF), specifically used in this embodiment: brand: TA-60512 / 0000, manufacturer: Solvay, USA, characteristic level: low viscosity, origin: USA, baking temperature: 120-180°C, baking time: 5 hours to 8 hours; Among them, the mass ratio between precursor, quantum dots and polymer is 82:3:15.
[0058] The preparation steps are: S1. Mix the precursors under an inert atmosphere, and put them into a zirconia ball mill together with 5 mm zirconia grinding balls, and perform ball milling in a planetary ball mill for 25 h, wherein the ball-to-material ratio is 23:1 and the rotation speed is 500 rpm to obtain a first ball milling product; Specifically, the molecular weight of Li2S is 45.942, and the molecular weight of P2S5 is 222.27. Then, the molar ratio of the three elements Li, P and S in Li2S and P2S5 with a mass ratio of 0.48:1 is about 2.32:1:3.66, and the first ball milling product is expressed as Li 2.32 PS 3.66 .
[0059] S2, under an inert atmosphere, the quantum dots and the first ball-milling product were placed together with 10 mm zirconia grinding balls in a zirconia ball milling jar, and high-energy mechanical grinding was performed in a vibration ball mill for 20 h, wherein the ball-to-material ratio was 20:1, the amplitude was 5 mm, and the vibration frequency was 1800 rpm to obtain a second ball-milling product; Specifically, the molecular weight of Ag2S is 247.8. After adding quantum dots, the molar ratio of the four elements Li, P, Ag and S in the second ball-milled product is about 2.32:1:0.05:3.69. The second ball-milled product is expressed as Li 2.32 PAG 0.05 S 3.69 .
[0060] S3, hot pressing and sintering the second ball-milled product in a muffle furnace under an inert atmosphere at a temperature of 240°C, a pressure of 420 MPa, and a sintering time of 7 h to obtain a sintered product; S4, crushing and grinding the sintered product under an inert atmosphere to increase the reaction area of the electrolyte powder. In this embodiment, a vertical roller mill is used to crush the sintered product at a roller speed of 70 rpm and a pressure of 3 MPa, and the crushed powder is sieved and classified to obtain an electrolyte powder with a particle size of 200-500 μm; S5. Mix solid electrolyte powder, polymer (as binder) and p-xylene (as solvent) in a mass ratio of 17:3:20 under an inert atmosphere. Then put them into a zirconia ball mill with 20 mm zirconia ball milling beads at a ball-to-material ratio of 10:1. Use a drum ball mill (Miqi horizontal DMS-4) to mix for 10 h at a speed of 300 rpm to ensure the uniformity of the mixed slurry. S6. Place the slurry in an inert atmosphere glove box, and use a coating machine to evenly coat the slurry on a copper strip using a scraper, wherein the copper strip is 10 μm, 9 cm wide, and 11 cm long, the scraper has a height of 220 μm, an angle of 90°, and a coating speed of 5 mm / s; S7. Dry the coated copper strip in an inert atmosphere at 70° C. for 6 h to form a composite solid electrolyte membrane on the copper strip. The composite solid electrolyte membrane has a thickness of 200 μm, a width of 8 cm, and a length of 10 cm.
[0061] It should be noted that, in this embodiment, the inert atmosphere is an argon environment with a water and oxygen content of ≤0.01 ppm.
[0062] Example 2 This embodiment provides a method for preparing a quantum dot CdS modified Li-Si-S composite sulfide solid electrolyte membrane, and the raw materials used include: Sulfide electrolyte precursor: Li2S and SiS2 with a mass ratio of 0.49:1; Quantum dots: CdS, average particle size 20 nm; Polymer: polyvinylidene fluoride; Among them, the mass ratio between precursor, quantum dots and polymer is 89:1:10.
[0063] The preparation steps are basically the same as those in Example 1, except that: In step S1, the first ball milling product obtained is represented by Li 1.97 SiS 2.98 ; In step S2, the second ball milling product is represented by Li 1.97 SiCd0.01 S 2.99 .
[0064] Example 3 This embodiment provides a method for preparing a quantum dot carbon nanotube modified Li-Si-S composite sulfide solid electrolyte membrane, and the raw materials used include: Sulfide electrolyte precursor: Li2S and SiS2 with a mass ratio of 0.49:1; Quantum dots: carbon nanotubes, average particle size 2.1 nm; Polymer: polyvinylidene fluoride; Among them, the mass ratio between precursor, quantum dots and polymer is 80:4:16.
[0065] The preparation steps are basically the same as those in Example 1, except that: In step S1, the first ball milling product obtained is represented by Li 1.97 SiS 2.98 ; In step S2, the second ball milling product is represented by Li 1.97 SiC 0.57 S 2.98 .
[0066] Example 4 This embodiment provides a method for preparing a quantum dot carbon nanotube modified Li-Ge-S composite sulfide solid electrolyte membrane, and the raw materials used include: Sulfide electrolyte precursor: Li2S and GeS2 with a mass ratio of 0.67:1; Quantum dots: carbon nanotubes, average particle size 2.1 nm; Polymer: polyvinylidene fluoride; Among them, the mass ratio between precursor, quantum dots and polymer is 85:4:11.
[0067] The preparation steps are basically the same as those in Example 1, except that: In step S1, the first ball milling product obtained is represented by Li 1.34 G JZ 2.67 ; In step S2, the second ball milling product is represented by Li 1.34 G JZ 0.30 S 2.67 .
[0068] Example 5 This embodiment provides a method for preparing a modified Li-PS composite sulfide solid electrolyte membrane, which is basically the same as the steps in Example 1, except that: In step S1, the precursor, quantum dots and zirconia grinding balls are put into a zirconia ball milling jar for ball milling, and the ball milling parameters are consistent; Cancel step S2.
[0069] Comparative Example 1 This embodiment provides a method for preparing a non-modified Li-PS composite sulfide solid electrolyte membrane, which is basically the same as the steps in Example 1, except that: In step S2, the first ball-milling product and zirconia grinding balls are put into a zirconia ball milling jar for ball milling, without quantum dots, and the ball milling parameters are consistent.
[0070] Comparative Example 2 This embodiment provides a Li - The preparation method of the Si-S composite sulfide solid electrolyte membrane is basically the same as the steps of Example 2, except that: In step S2, the first ball-milling product and zirconia grinding balls are put into a zirconia ball milling jar for ball milling, without quantum dots, and the ball milling parameters are consistent.
[0071] Comparative Example 3 This embodiment provides a method for preparing a non-modified Li-Ge-S composite sulfide solid electrolyte membrane, which is basically the same as the steps of Example 4, except that: In step S2, the first ball-milling product and zirconia grinding balls are put into a zirconia ball milling jar for ball milling, without quantum dots, and the ball milling parameters are consistent.
[0072] Battery Assembly Positive electrode sheet: The positive electrode material is NCM811, the positive electrode current collector is 10μm aluminum foil, and the binder is polyvinylidene fluoride. The mass ratio is 99:1. After mixing evenly, it is coated on the positive electrode current collector. The positive electrode material loading is 10 mg / cm 2 , the positive electrode is 8cm wide and 10cm long; Negative electrode sheet: The negative electrode material is a lithium-indium alloy negative electrode (indium foil, thickness is 200μm, lithium foil, thickness is 50μm), the negative electrode sheet is 8cm wide and 10cm long, and is attached to the negative electrode collector, which is a 10μm copper foil; Preparation of polymer electrolyte membrane: using the composite solid electrolyte membrane prepared by the above-mentioned embodiments and comparative examples; Battery assembly: In an inert atmosphere, the positive electrode, negative electrode and polymer electrolyte membrane are stacked together in sequence and then vacuum-sealed to assemble into an all-solid-state soft-pack lithium metal battery.
[0073] Parameter test conditions: The 200 μm thick electrolyte membrane was cut into 10 mm diameter discs and placed in a PEEK mold with stainless steel on both sides to measure the ionic conductivity and impedance. The test method was to use an electrochemical workstation EC-Lab, model VSP-300, with an initial potential of 0 V and a scan rate of 5 mV / s, from 0.1 Hz to 10 6 The test was carried out in the Hz range, and the sample ionic conductivity was measured according to the formula σ=l / (S*R), where l is the electrolyte thickness, S is the electrolyte cross-sectional area, and R represents the charge transfer resistance; Mechanical strength test: A tensile testing machine of the brand Litao, model LT, was used for testing at a tensile rate of 0.1mm / min. The test sample was a solid electrolyte membrane with a thickness of 200μm, a length of 2cm, and a width of 1cm.
[0074] It should be noted that the inert atmosphere of the assembly environment is an argon environment with a water and oxygen content of ≤0.01 ppm, and the test conditions are all in a constant temperature box at 25°C.
[0075] Performance Testing The XRD patterns of the electrolyte powders prepared in the examples and comparative examples are as follows: Figures 1 to 8 shown.
[0076] Figure 1 This is the XRD pattern of the electrolyte powder material prepared in Example 1. After analysis by XRD software, it was found that the synthesized material had characteristic peaks of Li3PS4 (PDF#04-010-1784 Li3PS4) and Ag2S (PDF#04-007-1178 Ag2S).
[0077] Figure 2 This is the XRD pattern of the electrolyte powder material prepared in Example 2. After XRD software analysis, it was found that the synthesized material had characteristic peaks of Li2SiS3 (PDF#04-005-3853 Li2SiS3) and Cd4SiS6 (PDF#04-002-4379 Cd4SiS6).
[0078] Figure 3 This is the XRD pattern of the electrolyte powder material prepared in Example 3. After analysis by XRD software, it was found that the synthesized material had some characteristic peaks of Li2SiS3 (PDF#04-005-3853 Li2SiS3) and carbon nanotubes (PDF#04-007-2081 CNTs).
[0079] Figure 4This is the XRD pattern of the electrolyte powder material prepared in Example 4. After analysis by XRD software, it was found that the synthesized material had characteristic peaks of Li4GeS4 (PDF#04-011-5080 Li4GeS4) and carbon nanotubes (PDF#04-007-2081 CNTs).
[0080] Figure 5 This is the XRD pattern of the electrolyte powder material prepared in Example 5. After analysis by XRD software, it was found that the synthesized material had characteristic peaks of Li3PS4 (PDF#04-010-1784 Li3PS4) and Ag2S (PDF#04-007-1178 Ag2S), which were much weaker than those in Example 1.
[0081] Figure 6 This is the XRD pattern of the electrolyte powder material prepared in Comparative Example 1. After XRD software analysis, it was found that the synthesized material had the characteristic peak of Li3PS4 (PDF#04-010-1784 Li3PS4).
[0082] Figure 7 This is the XRD pattern of the electrolyte powder material prepared in Comparative Example 2. After analysis by XRD software, it was found that the synthesized material had some characteristic peaks of Li2SiS3 (PDF#04-005-3853 Li2SiS3).
[0083] Figure 8 This is the XRD pattern of the electrolyte powder material prepared in Comparative Example 3. After analysis by XRD software, it is found that the synthesized material has the characteristic peak of Li4GeS4 (PDF#04-011-5080 Li4GeS4).
[0084] It should be noted that in Example 1, Li 2.32 PAG 0.05 S 3.69 The synthesis is carried out according to the stoichiometric ratio. The synthesized material is Ag2S doped on the basis of the crystal structure of Li3PS4. Although the existing material database is huge, it still cannot cover all known compounds and materials. Therefore, Li3PS4 is selected as the XRD comparison peak, and the newly added interstitial atoms will squeeze the surrounding atoms, causing the lattice constant to change, thereby shifting the position of the XRD peak. The same is true for other embodiments and comparative examples, which will not be repeated here.
[0085] The assembled battery was subjected to a cyclic discharge test at 0.1C, and the results of its first charge and discharge efficiency (first efficiency) and capacity retention after 100 cycles are listed in Table 1. It can be seen that after adding quantum dots to the solid electrolyte membrane, the first efficiency of the battery is improved by about 20%, which means that the energy conversion efficiency of the battery during the first charge and discharge process is improved and the energy loss is reduced.
[0086] When quantum dots were not added to the solid electrolyte membrane, the capacity retention rate of the battery in comparative example 1 after 39 cycles and the battery in comparative example 2 after 40 cycles was about 70%, while the capacity retention rate of the battery with quantum dots added after 100 cycles was above 90%. This shows that quantum dots can effectively improve the cycle stability of the battery, enable the battery to maintain a high capacity during long-term use, and extend the battery life.
[0087] The calculation formula of capacity retention rate is: .
[0088] Table 1 Battery performance test table corresponding to each embodiment and comparative example
[0089] The ionic conductivity was tested by the AC impedance method, and a tensile test was performed using a tensile machine to record the tensile force at break. The experimental data are shown in Table 2. It can be seen that the addition of quantum dots improves both ionic conductivity and mechanical properties, and reduces interface impedance. From the perspective of material performance, the role of quantum dots in batteries, electronic devices and other fields helps to improve the overall performance, efficiency and stability of equipment.
[0090] Table 2 Parameter test table corresponding to each embodiment and comparative example
[0091] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a composite sulfide solid electrolyte material, characterized in that: The following steps are involved: The precursor material and the quantum dot material are mixed, and then hot-pressed and sintered to obtain the composite sulfide solid electrolyte material, wherein: The mass ratio of the precursor material to the quantum dot material is 100: (1-10); The precursor material is a general formula Li x M y S b One or more of the sulfide materials shown are mixed, or the mixed sulfide materials have a general formula of Li x M y S b It is composed of two or more materials with the same element ratio, M is one of P, Si and Ge, x:y:b=(1.3~2.4) : 1 : (2.6~3.7); Quantum dot materials are metal compound quantum dots or carbon quantum dots with semiconductor properties.
2. The method for preparing the composite sulfide solid electrolyte material according to claim 1, characterized in that: The precursor material is prepared by mixing Li2S and a sulfide of an element M in a mass ratio of (0.45-0.7):1, where M is one of P, Si, and Ge.
3. The method for preparing the composite sulfide solid electrolyte material according to claim 1, characterized in that: Contains one or more of the following technical features: A. The metal compound quantum dots are metal sulfides; B. The carbon quantum dots are one or more of graphene quantum dots and carbon nanotube quantum dots.
4. The method for preparing the composite sulfide solid electrolyte material according to claim 3, characterized in that: The average particle size of the quantum dot material is 1-100 nm.
5. The method for preparing the composite sulfide solid electrolyte material according to claim 1, characterized in that: The parameters of the hot pressing sintering are: in an inert atmosphere, a pressure of 400-450 MPa, a temperature of 230-300° C., and a time of 4-7 h.
6. A composite sulfide solid electrolyte material, characterized in that: It is prepared by the method according to any one of claims 1 to 5, including the general formula Li x M y N c S z For the substance shown, M is one of P, Si, and Ge, N is one of Ag, Cd, Zn, Pb, and C, and x:y:c:z=(1.3~2.4) : 1 : (0.01~0.6) : (2.6~3.7).
7. The use of the composite sulfide solid electrolyte material according to claim 6 in manufacturing all-solid-state soft-pack batteries, characterized in that: The all-solid-state soft-pack battery comprises: a positive electrode, a negative electrode and an electrolyte membrane prepared from the composite sulfide solid electrolyte material.
8. A method for preparing a composite sulfide solid electrolyte membrane, characterized in that: It is prepared using the composite sulfide solid electrolyte material according to claim 6, comprising: A slurry obtained by mixing electrolyte powder, binder and solvent is coated on a substrate under an inert atmosphere, and after drying, the composite sulfide solid electrolyte membrane can be formed on the substrate. The electrolyte powder is obtained by grinding a solid electrolyte material, and the solid electrolyte material includes the composite sulfide solid electrolyte material described in claim 6.
9. The method for preparing a composite sulfide solid electrolyte membrane according to claim 8, characterized in that: Includes one or more of the following technical features: A. The electrolyte powder particle size is micron-sized; B. The grinding process is a roller crushing method, with a roller speed of 50-100 rpm and a pressure of 3-5 MPa.
10. The method for preparing a composite sulfide solid electrolyte membrane according to claim 9, characterized in that: Includes one or more of the following technical features: A. The mass ratio of the electrolyte powder, the binder and the solvent is (70-95): (5-30): 100; B. The binder is selected from one or more of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile and polymethyl methacrylate.
Citation Information
Patent Citations
Compound anode material, preparation method of compound anode material and all-solid lithium-sulphur battery
CN106784690A
Sulfide solid electrolyte, and preparation method and application thereof
CN110247109A
Functionalized quantum dot composite solid electrolyte membrane and preparation method and application thereof
CN110504486A
Lithium-lanthanum-zirconium-oxygen-based solid electrolyte and preparation method and application thereof
CN114725489A
Modified sulfide solid electrolyte, preparation method thereof and all-solid-state battery
CN116505059A